Exploration of physics teacher identity through life experience: A case study of science teacher with excellent achievement - Ellen Puspitaningtyas; Endang Purwaningsih; Supriyono Koes Handayanto (Universitas PGRI Kanjuruhan Malang, 2023)
This research aims to explore the construction of teacher identity through life experiences. Data were collected from observation, interviews, and document analysis. The subject of this study was TN (a pseudonym), who is a science teacher with an excellent academic background. The results of this research indicate that, from the perspective of discourse identity, TN is a teacher who emphasizes contextual learning and student-centered learning. Based on the perspective of nature identity, kinesthetic learning and her fondness for mathematics have had a major influence on her interest in physics. Meanwhile, from the perspective of affinity identity, family and role models greatly influence TN's beliefs about learning and her decision to have a career as a teacher. From the perspective of institutional identity, formal institutions have a negative impact on the construction of TN’s identities, while informal institutions such as organizations have a positive influence on TN's physics interests and rhetorical skills.